Functional matrix in the development of the facial skeleton in children - Makhlynets, Н. П.; Ozhohan, З. Р. (Actual Dentistry, 2022)
The aim of the study. Identifying the relationship between the presence of a bad habit and the violation of the formation of the facial skeleton in children. Improving the effectiveness of comprehensive treatment of patients with pathological occlusion and existing bad habits through orthodontic treatment and elimination of bad habits. Research methods. Examined and treated 15 patients aged 9–12 years (group I) and 15 patients aged 12–15 years (group II) with dental and maxillary anomalies and disorders of the architecture of the mouth against the background of bad habits. All patients underwent rehabilitation of the oral cavity, orthodontic treatment with removable and non removable structures, surgical correction of violations of the architecture of the oropharynx (freneloplasty, plastic connective tissue plastics). Conducted a clinical study, where the main point was the detection of abnormally attached bridles of the lips and tongue, the presence of connective tissue strands in the lateral group of teeth, changes in the dental-maxillary system due to bad habits. Computed tomography – to detect changes in the position of teeth and their rudiments, density and thickness of the bony structure of the jaw bones. We performed the following 3D-modeling of the facial skull and studied the cephalometric parameters of McNamara, the thickness of symmetrical masticatory muscles, analyzed the relationship between muscle thickness and bone thickness. We compared the changes in the photoprotocol before treatment, after treatment. Scientific novelty. Clinical studies have shown that 96.6 % of the examined patients (29 people) have bad habits. Patients who were able to overcome the bad habit were more likely to receive the desired therapeutic effect from the treatment based on the results of clinical and radiological examination, cephalometric analysis and photoprotocol. All patients before treatment had violations of the architecture of the oropharynx, manifested by highly attached strands in the area of the canines, premolars and bridle of the lip on the lower jaw (less than 5 mm); low-attached strands in the area of the canines, premolars and bridle of the lip on the upper jaw (less than 5 mm). Computed tomography data showed changes in the density and thickness of the bony structure of the jaw bones in areas where they were able to eliminate the bad habit. An increase in the thickness of the bony structure of the facial skull and an increase in the thickness of the masticatory muscles on the side where they managed to eliminate the bad habit were observed. Patients in groups I and II had a significant difference in cephalometric parameters according to McNamara before treatment and one year after the start of active treatment (p ≤ 0.05). The indicators in groups I and II did not differ significantly before treatment (p ≥ 0.05), but differed significantly one year after treatment (p ≤ 0.05), which is associated with the properties of bone structure at different ages of patients. Conclusions. Bad habits progress regardless of the patient's age, manifested in 96.6 % of patients.The results of clinical and radiological studies, analysis of cephalometric parameters and data on the thickness of the masticatory muscles confirm the relationship between chronic bad habits and the development of musculoskeletal system. The results indicate the ability of bone tissue to change its thickness, shape after the elimination of bad habits and confirm the presence of a functional matrix of bone structure. Bad habit is often one of the etiological factors in the development of pathological occlusion and only with its conscious elimination the patient achieves the desired therapeutic effect.